P-channel I-MOS transistor featuring silicon nano-wire with multiple-gates, strained Si1-yCy I-region, in situ doped Si 1-yCy source, and sub-5 mV/decade subthreshold swing - Toh, E.-H. (2014)
10.1109/VTSA.2008.4530781